Identification and characterization of a prokaryotic 6-4 photolyase from Synechococcus elongatus with a deazariboflavin antenna chromophore. Issue 10 (27th May 2022) - Chen, Simeng; Liu, Chenxi; Zhou, Chenchen; Wei, Zhihui; Li, Yuting; Xiong, Lei; Yan, Liang; Lv, Jun; Shen, Liang; Xu, Lei
Abstract: Synechococcus elongatus, formerly known as Anacystis nidulans, is a representative species of cyanobacteria. It is also a model organism for the study of photoreactivation, which can be fully photoreactivated even after receiving high UV doses. However, for a long time, only one photolyase was found in S. elongatus that is only able to photorepair UV induced cyclobutane pyrimidine dimers (CPDs) in DNA. Here, we characterize another photolyase in S. elongatus, which belongs to iron-sulfur bacterial cryptochromes and photolyases (FeS-BCP), a subtype of prokaryotic 6–4 photolyases. This photolyase was named Se PhrB that could efficiently photorepair 6–4 photoproducts in DNA. Chemical analyses revealed that Se PhrB contains a catalytic FAD cofactor and an iron-sulfur cluster. All of previously reported FeS-BCPs contain 6, 7-dimethyl-8-ribityllumazine (DMRL) as their antenna chromophores. Here, we first demonstrated that Se PhrB possesses 7, 8-didemethyl-8-hydroxy-5-deazariboflavin (8-HDF) as an antenna chromophore. Nevertheless, Se PhrB could be photoreduced without external electron donors. After being photoreduced, the reduced FAD cofactor in Se PhrB was extremely stable against air oxidation. These results suggest that FeS-BCPs are more diverse than expected which deserve further investigation.